A review of sustainable design in the automotive industry - Atef, Nagwaeen; Abdul Rahman, Julaila; Mohd. Din, Shamzani Affendy; Sapian, Abdul Razak (Kulliyah of Architecture and Enviromental Design, International Islamic University Malaysia, 2019)
To date, much research on the sustainability of the automotive industry has been published. The classification analysis method has been used to describe the relationship between sustainable design categories and the automotive industry. More than 50 articles related to sustainability towards the automotive industry were found from a search through a database on sustainability and automotive published between 2000 and 2018. This paper attempts to direct attention towards the user and responding to his needs when designing automobiles to help avoid over consumption. The findings show that the past articles discussed 1) improvement and actions taken; 2) the impact of fulfilling the users’ aesthetic and emotional needs; and 3) categories in sustainable products related to the automotive industry including green initiatives to sustainability, Malaysian industry and green initiatives, environmental aspects, sustainability in product life cycle, sustainable consumption, aesthetics and sustainability, end-life-remanufacturing, and product aesthetics, longevity, and user interaction. The study also found that sustainable design is considered less in meeting consumers’ emotional and aesthetic needs. This study could benefit from making early decisions during the automotive design and development process to avoid the costs and time used through later redesign, especially in Malaysia. As a whole, this paper contributes to encouraging manufacturers to adopt new thinking to support the environment by considering the influence of users’ aesthetic and emotional needs to improve the quality of the automotive industry